4‐bromopropofol decreases action potential generation in spinal neurons by inducing a glycine receptor‐mediated tonic conductance. (December 2014) - Eckle, V S; Grasshoff, C; Mirakaj, V; O'Neill, P M; Berry, N G; Leuwer, M; Antkowiak, B
<x xml:space="preserve">Abstract</x> Background and Purpose Impaired function of spinal strychnine‐sensitive glycine receptors gives rise to chronic pain states and movement disorders. Therefore, increased activity of glycine receptors should help to treat such disorders. Although compounds targeting glycine receptors with a high selectivity are lacking, halogenated analogues of propofol have recently been considered as potential candidates. Therefore we asked whether 4‐bromopropofol attenuated the excitability of spinal neurons by promoting glycine receptor‐dependent inhibition. Experimental Approach The actions of sub‐anaesthetic concentrations of propofol and 4‐bromopropofol were investigated in spinal tissue cultures prepared from mice. Drug‐induced alterations in action potential firing were monitored by extracellular multi‐unit recordings. The effects on GABAA and glycine receptor‐mediated inhibition were quantified by whole‐cell voltage‐clamp recordings. Key Results Low concentrations of 4‐bromopropofol (50 nM) reduced action potential activity of ventral horn neurons by about 30%, compared with sham‐treated slices. This effect was completely abolished by strychnine (1 μM). In voltage‐clamped neurons, 4‐bromopropofol activated glycine receptors, generating a tonic current of 65 ± 10 pA, while GABAA‐ and glycine receptor‐mediated synaptic transmission remained unaffected. Conclusions and Implications The highest glycine levels in the CNS are found in the ventral horn of the spinal cord, a region mediating pain‐induced motor reflexes and participating in the control of muscle tone. 4‐Bromopropofol may serve as a starting point for the development of non‐sedative, non‐addictive, muscle relaxants and analgesics to be used to treat low back pain.